Basic Literacy in Family Child in Growing Religious Character in Yogyakarta - Badriyah, Siti Laillatul; Fauziah, Pujiyanti (KnE Social Sciences, 2019)
This study aims to see changes in the religious character of children in RW 10 Kricak urban village, Yogyakarta. This study is a social action research. This research approach using a qualitative approach. Research data obtained by observation techniques, interviews and documentation. The result of the research is as follows. (1) social action planning consists of identifying the needs of the citizens. (2) the implementation of basic literacy program begins by preparing the management team, forming the learning and mentoring groups. (3) indicators of the success of basic literacy programs, that is developing the child’s religious character in the family. (4) the continuity of the basic literacy program as evidenced by the basic literacy program without the companion. Keywords: Education, Basic Literacy, Character, Family.